Pelatihan Asesmen Digital bagi Guru SMP untuk Meningkatkan Kualitas Evaluasi Pembelajaran : Digital Assessment Training for Middle School Teachers to Improve the Quality of Learning Evaluation - Husni Syahrudin; Junaidi H. Matsum; Nuraini Asriati; Heni Kuswanti; Syamsuri; Munawar Thoharudin; Dina Fitriana; Zuri Astari (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program was implemented to improve the competency of teachers at SMP Negeri 3 Pontianak City in understanding and implementing digital assessment as part of strengthening professionalism in the era of technology-based learning. The activity was developed through five stages, including initial data collection, pre-test, material delivery, practice and direct mentoring, and post-test. Evaluation results showed a significant increase in all indicators of participant understanding, including understanding of learning assessment (23% to 100%), instrument validity (23% to 91%), question difficulty level (41% to 95%), and utilization of interactive assessment media (73% to 86%). In addition, skills in operating the digital assessment platform also increased from 63% to 100%. These findings indicate that the training was able to strengthen the conceptual foundation and technical skills of teachers in designing and implementing accurate, interactive, and data-driven digital assessments. This program has implications for increasing teacher readiness in developing adaptive and relevant evaluation practices to the demands of 21st-century education